Metode Iterasi Tiga Langkah Bebas Turunan Untuk Menyelesaikan Persamaan Nonlinear - M. Nizam Nizam; Lendy Listia Nanda (UIN Sultan Syarif Kasim Riau, 2016)
This project, discusses modification Double Newton method combined with Liang Fang method,then removed all existing derivative in order to obtain the new iteration method to solve nonlinearequations. Analytically, indicated that the method has produced seven order of convergence. Numericalcomputation shows the resulting method is superior to the other methods discussed.Keywords: free derivative method, iterative method, nonlinear equations, order of convergence